Reducing the Software Value Gap. - PASS, SHIMEON; RONEN, BOAZ (Communications of the ACM, 2014)
The article focuses on methods of improving productivity and ensuring information technology (IT) value creation. It states that software development outsourcing and purchasing software packages both can involve a significant allocation of internal IT resources for systems analysis, integration with other software systems, data warehouses, data migration, and more. It comments on the use of Agile, Scrum, and Extreme Programming development methodologies to increase software development productivity and talks about the use of lean techniques to improve the cost effectiveness of IT organizations. It mentions the reuse of software and the use of critical chain methodology to reduce lead times for software development projects.